A 60° photonic crystal waveguide bend with improved transmission characteristics - Khatibi Moghaddam, Malihe; Mirsalehi, Mir Mojtaba; Attari, Amir Reza (Oficyna Wydawnicza Politechniki Wrocławskiej, 2009)
In this paper, a 60° waveguide bend is designed in a two-dimensional (2D) photonic crystal (PC) slab to provide high transmission over a large bandwidth. We apply geometrical modification in the bend region to improve the transmission characteristics. This modification results in increasing the relative bandwidth from 6.5% to 25.7% of photonic band gap width. Using the effective refractive index, the structures designed are simulated by the 2D finite-difference time-domain (FDTD) method. As a specific application, we use the improved bend structure in a PC waveguide directional coupler and show that the drop output increases significantly.
Optica Applicata, Vol. 39, 2009, nr 2, s. 307-317
Keywords: optyka; photonic crystal; waveguide; bend; bandwidth; slab structures